Penitentiary crime in Kazakhstan: growth factors and preventive measures - Kemeshov, R.S.; Muratova, A.Zh.; Turegeldiyev , B.U. (BULLETIN of L.N. Gumilyov Eurasian National University Law Series, 2024)
The study is devoted to the analysis of factors contributing to the growth of penitentiary crime in Kazakhstan and the development of comprehensive prevention measures. It considers the social, economic, institutional and legal aspects of the problem as well as the international experience of reforming penitentiary systems. The work identifies systemic problems that hinder the effective re-socialization of convicts, such as overcrowding in prisons, unsatisfactory conditions of detention, lack of social programs, corruption and gaps in legislation. The practical significance of the study lies in offering specific recommendations for improving legislation, improving conditions of detention and developing re-socialization programs. The research methods include comparative analysis, statistical generalization and expert assessments based on data from normative legal acts, reports of international organizations and scientific publications. The necessity of improving the legal mechanisms regulating the penitentiary system, taking into account international human rights standards, has been identified. The study contributes to criminological science by offering a detailed analysis of penitentiary crime in Kazakhstan. Its results can be useful for government agencies in developing crime prevention strategies and improving the conditions of detention of convicts.